Prevalence of unfavorable outcome in acute poisoning and associated factors at the University of Gondar comprehensive specialized hospital, Gondar, Northwest Ethiopia: a hospital-based cross-sectional study - Waktola, Leta Gemeda; Melese, Endalkachew Belayneh; Mesfin, Nebiyu; Altaye, Kassaye Demeke; Legese, Gebrehiwot Lema (Frontiers in Public Health, 2023)
Background Acute poisoning is a medical emergency in which the toxic effects occur almost immediately, usually within hours from the time of exposure, and can result from exposure to excessive doses of any chemical. It is the common cause of emergency admission, which may result in morbidity and mortality. There are a lot of factors that are associated with an increased magnitude of mortality and complication. Therefore, this study was carried out to assess the clinical characteristics of patients, unfavorable outcomes of acute poisoning, and associated factors to improve the quality of care, resource utilization, and decrease mortality. Objective This study aimed to assess the outcome and associated factors among acute poisoning patients at the University of Gondar Comprehensive Specialized Hospital, Gondar, Northwest Ethiopia (2021). Methods A prospective follow-up study was conducted from January 2021 to September 2021 at the University of Gondar Comprehensive Specialized Hospital, Gondar, Northwest Ethiopia. Data were collected using a comprehensively organized and pretested interviewer-administered questionnaire. The data were entered using EPI data version 4.6.0 statistical software and then exported to Stata 14 for analysis. The data were analyzed for descriptive statistics. Statistical analysis was performed using bivariate and multivariate logistic regression models to identify factors associated with the unfavorable outcome of acute poisoning. The result is presented in the form of tables, figures, and text using frequencies and summary statistics such as mean, SD, median, IQR, and percentage. Result A total of 233 patients were included in the study. The prevalence of unfavorable poisoning outcomes in acute poisoning was 17.6% (95% CI: 13.2, 23.1). In the multivariate logistic regression analysis, known chronic medical comorbidities [AOR: 3.846 (1.619, 9.574); value of p: 0.014] and hospital stay of less than 48 h [AOR: 6.57 (2.03, 21.273); value of p: 0.002] were found to be independent factors associated with unfavorable outcomes in acute poisoning. Conclusion The magnitude of unfavorable poisoning outcomes was high in patients with acute poisoning. Having known medical comorbid illness and short hospital stay of less than 48 h were found to be associated with unfavorable outcomes.